MicroRNA-155 Tissue Expression in Patients with Breast Cancer at Dr Haji Adam Malik Hospital, Medan - Ompusunggu, Henny Erina Saurmauli; -, Juwita; Nauphar, Donny; Pardede, Sumondang M.; Lim, Hadyanto; Siregar, Yahwardiah (Indonesian Journal of Medicine, 2016)
Background: MicroRNA (miRNA) is noncoding-RNA that comprises 18-22 nucleotides. miRNA binds its gene targets in the 3-untranslated region (3-UTR), causing direct degradation of mRNA and repressed translation of RNA. MicroRNA regulates various biological processes, including cell proliferation, apoptosis, cell growth, cell differentiation, and metabolism. Various changes have been identified miRNA expression in different types of cancers. This study aimed to describe the expression of miR-155 in patients with breast cancer tissue in Haji Adam Malik Hospital in Medan.Subjects and Method: This was a descriptive study. A total sample was 64 paraffin tissue blocks was taken from female patients with breast cancer at the surgical oncology unit, Haji Adam Malik Hospital in 2013-2014. RNA sample were isolated and checked using a spectrophotometer followed by cDNA synthesis. Then this sample was analyzed for miR-155 expression by using Real Time qPCR. Histopathological grade data were obtained from the medical record.Results: The miR-155 expression in the breast cancer patients is higher than that in the UniSp6 RNA Spike-in (internal controls). miR-155 expression was 29.64, 28.44, 29.22, in grade-I, grade-II, grade-III breast cancer, respectively. UniSp6 RNA Spike-in was 22.30, 22.89, 23.10, respectively in the control groups. Thus, increased of miR-155 expression was the highest in grade I breast cancer patients.Conclusion: Increased miR-155 expression can be used as a biomarker for early diagnosis and prognosis of breast cancer.Keywords: miRNA, miR-155, breast cancer.Correspondence: Henny Erina Saurmauli Ompusunggu. Department of Cellular and Molecular Biology, Faculty of Medicine, HKBP Nommensen University, Medan. Email: ompusunggu.henny@gmail.comIndonesian Journal of Medicine (2016), 1(1): 20-25https://doi.org/10.26911/theijmed.2016.01.01.03